Martensia incipiens (Delesseriaceae, Rhodophyta), a newly recognized species of red algae from the Sultanate of Oman - Wynne, Michael J. (Phytotaxa, 2019)
Martensia incipiens sp. nov. is described from the Sultanate of Oman, based upon collections made in the Governate of Dhofar, Northern Arabian Sea. The type locality is Sadah. The delicate blades display a dazzling iridescence with pink to lilac colors in the living condition. The distinguishing morphological feature of this novel species is that the latticework is confined to a very narrow marginal fringe, consisting of vertical files of only six to nine cells in length and without any cross-links between the vertical files. Putative young tetrasporangial sori have a scattered arrangement over the blades.